Peningkatan Hasil Belajar Siswa Fase E Melalui Problem Based Learning Pada Materi Manusia Mahluk Pribadi Di SMA Negeri 1 Sokan, Kabupaten Melawi - Heribertus Harianto Wuda (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia is experiencing very dynamic developments and changes which are in accordance with the noble ideals of the nation as regulated in the 1945 Constitution article 31 paragraphs 1-4 which states that every citizen has the right to education, every citizen is obliged to attend basic education and the government is obliged to finance it. Education is a complex series of events. This event is a series of communication activities between humans and other elements, so that humans develop as individuals. Education is also explained in the National Education System Law Number 20 of 2003 article 3 regarding the function and objectives of education, namely developing abilities and forming a dignified national character and civilization in order to make the life of the nation intelligent and aims to develop the potential of students to become human beings who believe. and have faith in God Almighty, have noble character, be competent, creative, independent and be citizens of a democratic and responsible country. This then became one of the aspirations of SMA Negeri 1 Sokan to form and develop students so that they not only progress together and succeed together but more than that are able to become students who are useful for society in particular and the country and the nation in general.